(untitled) (Global Journal of Management and Business Research, 2025)
Abstract- There is growing recognition of the central role corporate governance plays in providing specialized services that align firms towards accountable and transparent financial practices What is not clear however is the conditional effect of corporate governance on the causal link involving internal financing and financial performance Therefore this study exploits the principles underlying the Agency and Pecking Order Theories to probe how corporate governance conditions the effect of retained earnings a popular internal financing source on the financial performance of real-sector non-financial firms listed at the Nairobi Securities Exchange NSE The study employs a causal-explanatory design that targets 51 real-sector non-financial firms listed at the NSE A sampling frame defined for the period 2016 to 2022 inclusive is used to identify 42 firms with complete and suitable financial records that constituted the secondary data After running the relevant diagnostic tests retained earnings had a positive and significant direct effect on financial performance b 0 653 p 0 001 This effect however diminishes on introducing corporate governance The interaction between retained earnings and corporate governance was positive and significant b 0 263 p 0 05 an indication that corporate governance strengthened the dynamics of internal financing on financial performance However on its own corporate governance impacted financial performance negatively showing that embracing corporate governance may be counterproductive in the short term depending on the firm s context